Conversations about Religion - Burton, Howard (Ideas Roadshow Collections., 2021)
Conversations About Religion is a five-part Ideas Roadshow Collection of carefully-edited Ideas Roadshow Conversations featuring leading experts with a detailed preface highlighting the connections between the different books. All five books include a detailed essay setting up the different ideas and questions for discussion at the end of each chapter. The following experts have participated in this Collection: 1. David J. Goldberg (1939-2019), former Senior Rabbi Emeritus of London's Liberal Jewish Synagogue and author and columnist; 2. Nile Green who holds the Ibn Khaldn Endowed Chair in Wor.